Metode Pembelajaran Masa Kekhalifahan Abbasiyah - Dhaiman, Arif Noor; Hidayat, Tatang; Istianah, Istianah (PT. Student Rihlah Indonesia, 2023)
The purpose of this study is to find out the learning methods of the Abbasid Caliphate. The research method used is qualitative with a literacy study approach. The results show that the 'ilmiyyah learning method is directed to form a level or type of deep thinking, but it is not allowed to release the spirit of the teaching-learning process in the theme of creation, khashiyyah (characteristics of objects and potential for life), and utilization according to shara' law